Old beagle dogs have lower faecal concentrations of some fermentation products and lower peripheral lymphocyte counts than young adult beagles - Sampaio Gomes, Marcia de Oliveira [UNESP]; Beraldo, Mariana Casteleti [UNESP]; Putarov, Thaila Cristina [UNESP]; Brunetto, Marcio Antonio [UNESP]; Zaine, Leandro [UNESP]; Abreu Gloria, Maria Beatriz; Carciofi, Aulus Cavalieri [UNESP] (Cambridge University Press, 2011)
The effects of age on microbiota composition, gut fermentation end-product formation and peripheral lymphocyte numbers were compared between old and young adult Beagle dogs fed four kibble diets differing in yeast cell wall contents. The experiment had a double 4 x 4 Latin square design, one with four mature dogs (4 years old) and the other with four old dogs (10 years old), with four replicates (diets) per dog. In each period a 15d adaptation period preceded a 5d total collection of faeces for the digestibility trial. on day 21, fresh faecal samples were collected for the determination of bacterial enumeration, pH, biogenic amine and short-chain fatty acid. Flow cytometry was used for immunophenotypic evaluation. Dogs were fed four kibble diets with similar composition with 0, 0.15, 0.30 and 0.45% of yeast cell wall (as-fed), respectively. Data were evaluated using general linear models of Statistical Analysis Systems statistical software (P<0.05). No evidence of a difference in faecal bacteria counts between ages was found (total aerobes, total anaerobes, Bifidobacterium, Lactobacillus, Clostridium and Escherichia coli: P. 0.15). Faecal concentrations of butyrate, histamine, agmatine and spermine were lower (P <= 0.05) and faecal pH was higher (P=0.03) in older dogs than in mature adult dogs, suggesting an alteration in bacterial metabolic activity, or in the rate of intestinal absorption of these compounds. Concentrations of T-lymphocytes, T-cytotoxic lymphocytes and B-lymphocytes were also lower (P <= 0.01) in older dogs than in mature adult dogs. The study confirmed alterations in peripheral lymphocytes and revealed a reduced concentration of some fermentation end products in the colon of old dogs.
Keywords: Biogenic amines; Butyrate; Digestibility; Microbiota